DISPUTE ON LEASE FINANCING AGREEMENT: IS IT SUBJECT TO CONSUMER PROTECTION OR CIVIL LAW? - Hakim Manurung, Jefferson (Jurnal Hukum dan Peradilan, 2022)
Disputes arising between the financing company and the debtor in connection with the implementation of the lease financing agreement often occur as the debtor is negligent in completing the installments as contained therein. Consequently, the financing company withdraws the object of financing that is encumbered with security, generally with a fiduciary, from the possession of the debtor. Upon this action, the debtor filed a lawsuit against the financing company to the BPSK since the debtor considered themselves as consumers in the lease financing agreement, so that in some cases BPSK won the debtor's lawsuit. However, both the district court and the Supreme Court of the Republic of Indonesia in their decisions emphasized that this is not a consumer dispute, but a civil dispute in the form of breach of contract. The research in this article will answer whether the dispute between the financing company and the debtor in regard to lease financing agreement will be subject to the consumer protection law or civil law and which judicial bodies has the authority to settle this issue. The research method used in this research is normative juridical with analytical descriptive research specifications. The data used in this study are secondary data and tertiary data that have been prepared and analyzed according to the topic of discussion in this article. The main finding in this study is the agreement in the financing agreement because there is a breach of contract that is subject to civil law and the court that adjudicates it is the district court and not the BPSK.Perselisihan yang timbul antara perusahaan pembiayaan dengan debitur sehubungan dengan pelaksanaan perjanjian pembiayaan seringkali diakibatkan karena debitur lalai dalam menyelesaikan angsuran sebagaimana diperjanjikan dalam perjanjian tersebut. Oleh karena itu, perusahaan pembiayaan menarik objek pembiayaan yang dibebankan jaminan kebendaan, umumnya dengan fidusia, dari penguasaan debitur. Atas tindakan tersebut, debitur mengajukan gugatan kepada BPSK karena debitur menganggap bahwa mereka adalah konsumen dalam perjanjian pembiayaan sehingga dalam beberapa kasus BPSK memenangkan gugatan debitur. Namun, pengadilan negeri maupun Mahkamah Agung dalam putusannya menegaskan bahwa perselisihan ini bukan merupakan sengketa konsumen, melainkan sengketa keperdataan berupa cidera janji.Â  Penelitian dalam artikel ini akan menjawab mengenai apakah perselisihan antara perusahaan pembiayaan dan debitur dalam perjanjian pembiayaan tunduk pada hukum perlindungan konsumen atau hukum perdata serta badan peradilan mana yang berwenang menyelesaikan perselisihan ini. Metode penelitian yang digunakan dalam penelitian ini adalah yuridis normative dengan spesifikasi penelitian deskriptis analitis. Data yang digunakan dalam penelitian ini merupakan data sekunder dan data tersier yang telah disiapkan dan dianalisis sesuai dengan topik diskusi dalam artikel ini. Temuan utama dalam penelitian ini adalah perselisihan dalam perjanjian pembiayaan dikarenakan adanya peristiwa cidera janji tunduk pada hukum perdata serta badan peradilanÂ  yang berwenang mengadiliinya adalan pengadilan negeri dan bukan BPSK.Â